Perbandingan Kinerja Keuangan Sebelum dan Sesudah Implementasi Enterprise Resource Planning (ERP) pada Perusahaan yang terdaftar di Bursa Efek Indonesia - Gina Kholidayanti; Maslichah Maslichah; Irma Hidayati (Universitas Islam Malang, 2023)
This research was conducted to analyze differences in company financial performance before and after ERP implementation. The Enterprise Resource Planning system can be defined as a concept, technique, or method for integrating all departments and functions of a company into an entire business process automation system in order to increase the effectiveness and efficiency of the company as reflected by the existence of an accurate financial report. truly reflects the existing situation and conditions. This study uses 3 variables, namely ROA, ROE, and NPM. This study used a purposive sampling method in selecting the sample, with the sample criteria being companies registered on the IDX and implementing the Enterprise Resource Planning system in 2012. Based on these criteria, a sample of 4 companies was obtained for 3 (three) years before and 3 (three) years after implementation. This research was conducted using quantitative methods and the analytical techniques used were descriptive statistical analysis and hypothesis testing using paired sample t tests. The results of the study show that not all performance is affected by the implementation of Enterprise Resource Planning. Only Return on Assets and Net Profit Margins have significant changes after the implementation of the Enterprise Resource Planning system.Keywords: Enterprise resource planning, company financial performance, return on assets, return on equity, net profit margin.